A High-Performance Three-Dimensional Hierarchical Structure MOF-Derived NiCo LDH Nanosheets for Non-Enzymatic Glucose Detection. Issue 16 (3rd January 2019) - Song, Dandan; Wang, Lili; Qu, Yuning; Wang, Bing; Li, Yanting; Miao, Xueli; Yang, Yuying; Duan, Cunpeng
Abstract : Constructing a reasonable electrode material structure is significant for the sensitivity and selectivity of glucose detection. Herein, in this paper, the three-dimensional (3D) hierarchically layered double hydroxides (CC@CCH MOF LDH) is prepared by using carbon cloth (CC) as the conductive base, cobalt carbonate nanorod (CCH) as the guiding template and metal organic framework (MOF) as the sacrifice template. This unique 3D hierarchical structure facilitates the rapid transfer of ions and the reversible redox reaction. Moreover, the electrochemical tests confirm that the material has excellent electrocatalytic oxidation activity in alkaline solution. The amperometric detection results reveal that CC@CCH MOF LDH electrode material possesses better selectivity, higher sensitivity (4310 μA·mM −1 ·cm −2 ), fast amperometric response (<6 s), wide linear range (0.001-2 mM) and low detection limit (110 nM) under the optimal conditions, which is expected to be a high performance enzyme-free glucose sensor.